2014
DOI: 10.3109/02770903.2014.888573
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an indoor intermittent training program for improving lung function, physical capacity, body composition and quality of life in children with asthma

Abstract: An indoor intermittent training program with these characteristics has improved lung function, physical capacity, body composition and quality of life in children with asthma. These training adaptations are particularly relevant for those patients suffering from asthma as a regular physical exercise routine will greatly improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 24 publications
3
53
1
4
Order By: Relevance
“…Whilst the present study is consistent with the majority of the literature which similarly found that exercise did not affect lung function (Wanrooij et al, 2014), it is pertinent to note that two studies reported a significant increase in FEV1% (8-20%), both of which implemented intermittent training (Latorre-Roman et al, 2014, Sidiropoulou et al, 2007. This discrepancy may, in part, be related to the severity of asthma, with the majority of participants in this study having mild asthma, or to the intervention duration; although longer than many previous studies (Moreira et al, 2008, Wicher et al, 2010, 6-months may have been insufficient to elicit significant adaptations in lung function.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Whilst the present study is consistent with the majority of the literature which similarly found that exercise did not affect lung function (Wanrooij et al, 2014), it is pertinent to note that two studies reported a significant increase in FEV1% (8-20%), both of which implemented intermittent training (Latorre-Roman et al, 2014, Sidiropoulou et al, 2007. This discrepancy may, in part, be related to the severity of asthma, with the majority of participants in this study having mild asthma, or to the intervention duration; although longer than many previous studies (Moreira et al, 2008, Wicher et al, 2010, 6-months may have been insufficient to elicit significant adaptations in lung function.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, as 70% of the participants were on inhaled corticosteroids, this may have masked any potential exercise effects. Interestingly, although weight reduction has previously been shown to improve lung function in the obese/overweight (Latorre-Roman et al, 2014), within the present study, the increase in BMI in the control group did not manifest in any reduction in lung function. Consequently, future studies incorporating a longer duration intervention should endeavour to clarify effects on BMI and lung function.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…These limitations seemed to be a common feature among adolescents with asthma and showed that it is important that health care professionals focus on physical function when providing asthma care in adolescence. Studies have shown that physical activity improves quality of life among children and adolescents with asthma (162,163).…”
Section: Daily Life With Asthma (Studies III and Iv)mentioning
confidence: 99%